Цифрова економіка та трансформація традиційних індустрій: виклики та можливості інституціоналізації цифрової економіки - Звонар, Віктор Павлович; Решетняк, Наталя Борисівна; Томах, Вікторія Володимирівна (ТОВ "Міжнародний бізнес центр", 2024)
Цифрова економіка нині є фактором успіху трансформації традиційних індустрій, проте її впровадження має як можливості, так і виклики в аспекті інституціоналізації. Цифрова трансформація приносить підприємствам традиційних індустрій як можливості, так і виклики. Розв’язання проблем у досліджених чотирьох головних детермінантів інституціоналізації цифрової економіки допоможуть створити умови для переходу більшості підприємств до цифрових технологій у виробництві та управлінні.

Introduction. The digital economy is now a success factor in the transformation of traditional industries such as manufacturing, agriculture, construction, transportation and logistics, finance, and trade. However, its implementation presents both opportunities and challenges in terms of institutionalization, with relevant implications for businesses. The purpose of the paper is to analyse the possible challenges and opportunities for the institutionalization of the digital economy in Ukraine and research into measures that could improve the current situation. Results. Digital transformation brings both opportunities and challenges to traditional industries. All the opportunities that digitalization brings to companies in digital industries have been conditionally grouped into four groups: globalization, emergence of new customer segments, use of cloud solutions, artificial intelligence and blockchain technologies in production and management aspects of the company. The challenges that pose the greatest risks in the process of implementing digital technologies and tools are the slow pace of digitalization, lack of innovation, and insufficient data reliability. However, for the effective implementation of digital transformation, the state should develop four main elements of institutionalization of the digital economy: infrastructure, legal regulation, employee training, and financing. Imperfect legal regulation, insufficient digital literacy of employees, underdeveloped infrastructure, especially the Internet, and insufficient financing are slowing down the digitalization process in traditional industrial enterprises in Ukraine. Conclusion. Solving the problems in the four main determinants of the institutionalization of the digital economy will help Ukraine create conditions for an effective transition of most enterprises in traditional industries to digital technologies in production and management, benefiting both the Ukrainian economy and the enterprises themselves.
Digital economy and the transformation of traditional industries: challenges and opportunities for institutionalizing the digital economy
Keywords: цифрова економіка; трансформація індустрій; традиційні індустрії; виклики; можливості; digital economy; industry transformation; traditional industries; challenges; opportunities